2012
DOI: 10.1111/j.1440-1843.2011.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a semi‐quantitative procalcitonin test and the A‐DROP Japanese prognostic scale for predicting mortality among adults hospitalized with community‐acquired pneumonia

Abstract: The semi-quantitative PCT test and the A-DROP scale were found to be useful for predicting mortality in adult patients with CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
2
31
1
Order By: Relevance
“…In contrast to the results of the present study, Kasamatsu et al 9 showed that the semi-quantitative procalcitonin measurement was useful for predicting mortality from CAP. We can propose 2 possible explanations for this discrepancy.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to the results of the present study, Kasamatsu et al 9 showed that the semi-quantitative procalcitonin measurement was useful for predicting mortality from CAP. We can propose 2 possible explanations for this discrepancy.…”
Section: Discussioncontrasting
confidence: 54%
“…However, there are few data on the usefulness of the semi-quantitative serum procalcitonin test for predicting clinical outcomes of patients with CAP. To our knowledge, only one report, by Kasamatsu et al, 9 showed that the semi-quantitative procalcitonin test was useful for predicting mortality from CAP, but it was not as useful as the Pneumonia Severity Index, CURB-65 scale, and A-DROP scale. In short, the significance of performing this semiquantitative serum procalcitonin test on patients with CAP has not yet been adequately revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Kasamatsu et al, have studied the predictive ability of baseline serum PCT for mortality using the semiquantitative kits and compared it to the A DROP, CURB-65 and PSI scores. They found that baseline serum PCT levels were positively correlated with the PSI and the CURB-65 [25]. They concluded that the baseline serum PCT level is useful for predicting 30 day mortality in adult patients with CAP which is similar to our findings.…”
Section: Discussionsupporting
confidence: 81%
“…The sensitivity and specificity of procalcitonin of ≥ 2ng/ml to predict 30 day mortality was 100% and 73.47% respectively, the negative predictive value was 100 and the area under receiver operating characteristics curve was 0.92 (0.85 -1.0). Kasamatsu Yu et al, in his study using similar semi-quantitative test with a cut off of ≥ 0.5ng/ml reported AUC for predicting 30 day mortality with PCT as 0.80 (0.70 -0.90) [25]. A study by Kim et al, showed that the odds ratio for severe pneumonia showed a seven to eight fold increase for PSI and CURB-65 at PCT level of ≥ 2.0 ng/ ml and the odds ratio for mortality had seven fold increase with PCT > 10ng/ml [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate an association between elevated PCT and mortality in septic patients [17, 18]. Although the addition of initial PCT to clinical indices improves prognostic performance of severity scores [19, 20], a large European study failed to validate these findings [21].…”
mentioning
confidence: 99%